Dehydrogenation catalyst with minimized aromatics production

By using a layered catalyst composition, including the outer layer and inner core of transition alumina, uniformly dispersing the platinum group metal and accelerator metal, the problems of low selectivity of n-olefins and high selectivity of aromatic compounds in the existing hydrocarbon dehydrogenation process are solved. , achieving a more efficient hydrocarbon dehydrogenation process.

CN115379895BActive Publication Date: 2025-02-25UOP LLC
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202180026963.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-13
Filing Date
2021-03-05
Publication Date
2025-02-25
Estimated Expiration
2041-03-05

AI Technical Summary

Technical Problem

In the existing hydrocarbon dehydrogenation methods, the selectivity of total n-olefins is low, while the selectivity of undesirable aromatic compounds is high, resulting in poor product quality.

Method used

The layered catalyst composition is adopted, including the inner core and the outer layer, which is composed of transitional alumina, has a specific diffraction angle peak between 32.0°2θ and 70.0°2θ, and is uniformly dispersed in the outer layer, Accelerator metal and modifier metal.

Benefits of technology

The selectivity of total n-olefins is improved, the selectivity of undesirable aromatic compounds is reduced, and the product quality is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115379895B_ABST
    Figure CN115379895B_ABST
Patent Text Reader

Abstract

Catalyst composition and its use as a dehydrogenation catalyst to increase the selectivity of normal olefins and reduce the undesirable selectivity of aromatic compounds. The reduction in the production of aromatic compounds allows the elimination of units for removing aromatic compounds. The catalyst has a layered composition, which comprises an inner core, an outer layer bonded to the inner core, the outer layer comprises one or more transition aluminas, the transition aluminas have at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak in the range is at 32.7±0.4°2θ, and the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a thickness of less than 100 microns and has a platinum catalyst and at least one promoter metal uniformly dispersed thereon, and the concentration of the platinum catalyst is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of surface area of ​​the outer layer based on the element.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority declaration

[0002] This application claims priority to U.S. application No. 16 / 818,061, filed on March 13, 2020, which is incorporated herein in its entirety.

[0003] The present invention relates to a hydrocarbon dehydrogenation process using a layered catalyst composition under operating conditions selected to increase overall normal olefin selectivity and reduce undesirable aromatic compound selectivity.

[0004] Platinum-based catalysts are used in a variety of hydrocarbon conversion processes. Promoters and modifiers are also used in many applications. One such hydrocarbon conversion process is the dehydrogenation of hydrocarbons (specifically alkanes, such as isobutane converted to isobutylene). For example, U.S. Patent No. 3,878,131 (and related U.S. Patent Nos. 3,632,503 and 3,755,481) discloses a catalyst comprising platinum metal, tin oxide components and germanium oxide components. All components are uniformly dispersed throughout the alumina carrier. U.S. Patent No. 3,761,531 (and related U.S. Patent No. 3,682,838) discloses a catalytic composite material comprising a platinum group component, a Group IVA (IUPAC 14) metal component (e.g., germanium), a Group VA (IUPAC 15) metal component (e.g., arsenic, antimony) and an alkali metal or alkaline earth metal component, all of which are dispersed on an alumina carrier material. Similarly, all components are uniformly distributed on the carrier.

[0005] U.S. Patent 6,177,381 describes a layered catalyst composition and a method for preparing the catalyst. Example 7 of U.S. Patent 6,177,381 describes the dehydrogenation activity of catalysts A, B, E and F tested using hydrocarbon feed. A water concentration of 2000 ppm based on the weight of hydrocarbon was injected. The deactivation rates of catalysts A, B, E and F were 0.052°F / hr, 0.032°F / hr, 0.050°F / hr and 0.033°F / hr, respectively.

[0006] U.S. Patent 6,756,515 describes a dehydrogenation process using a layered catalyst composition comprising an inner core such as alpha-alumina and an outer layer of an outer refractory inorganic oxide such as gamma-alumina bonded to the inner core. The outer layer has a platinum group metal such as platinum and a promoter metal such as tin uniformly dispersed thereon. The composition is an effective catalyst, but it is desirable to develop catalysts and methods that improve the yield of total normal olefins and reduce the undesirable aromatic compounds that need to be removed. Summary of the invention

[0007] The present invention relates to a catalyst composite material, which has a layered composition, the layered composition comprises an inner core, an outer layer bonded to the inner core, the outer layer comprises one or more transition aluminas, the transition aluminas have at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak in the range is at 32.7±0.4°2θ, and the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a thickness of less than 100 microns and has at least one platinum group metal and at least one promoter metal uniformly dispersed thereon, and the concentration of the at least one platinum group metal is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of surface area of ​​the outer layer on an elemental basis, the layered composition also has at least one modifier metal dispersed thereon, and the inner core refractory inorganic oxide and the outer refractory inorganic oxide are different materials.

[0008] In a broad embodiment, the present invention is a hydrocarbon dehydrogenation method comprising contacting a hydrocarbon stream with a layered composition under dehydrogenation conditions to obtain a dehydrogenated product, the layered composition comprising an inner core, an outer layer bonded to the inner core, the outer layer comprising one or more transition aluminas, the transition aluminas having at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak within the range is at 32.7±0.4°2θ, the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a diffraction angle of less than 100°2θ. The layered composition has a thickness of microns and has a platinum catalyst and at least one promoter metal uniformly dispersed thereon, and the concentration of the platinum catalyst is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of the surface area of ​​the outer layer on an elemental basis, the layered composition also has at least one modifier metal dispersed thereon, the inner core refractory inorganic oxide and the outer refractory inorganic oxide are different materials, and the layered composition also has a loading of at least one platinum group metal of 0.0010 grams to 0.0060 grams of platinum group metal per cubic centimeter of the layered composition on an elemental basis. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The accompanying figures show X-ray diffraction of the materials prepared in Examples 1 to 3 and of two different forms of aluminium oxide. DETAILED DESCRIPTION

[0010] The present invention relates to a dehydrogenation method using a layered catalyst composition. The layered catalyst composition comprises an inner core composed of a material having a significantly lower adsorption capacity relative to an outer layer. Some inner core materials are also substantially impermeable to liquids, for example, metals, including but not limited to aluminum, titanium and zirconium. Examples of inner core materials include but are not limited to refractory inorganic oxides, silicon carbide and metals. Examples of refractory inorganic oxides include but are not limited to alpha alumina, theta alumina, cordierite, zirconium oxide, titanium dioxide and mixtures thereof. A preferred inorganic oxide is alpha alumina.

[0011] These materials forming the kernel can be formed into various shapes, such as pellets, extrudates, spheres or irregularly shaped particles, but not all materials can be formed into each shape. The preparation of the kernel can be carried out by methods known in the art, such as oil droplets, pressure molding, metal forming, granulation, granulation, extrusion, rolling methods and spherical granulation. Spherical kernels are preferred. The kernel (whether spherical or not) has an effective diameter of 0.05mm to 5mm, and preferably 0.8mm to 3mm. For non-spherical kernels, the effective diameter is defined as the diameter of the shaped article when it is molded into a sphere. Once the kernel is prepared, it is calcined at a temperature of 400°C to 1500°C.

[0012] The inner core is now coated with a layer of a refractory inorganic oxide which is different from the inorganic oxide which may be used as the inner core and will be referred to as the outer refractory inorganic oxide. This outer refractory oxide is a layer of good porosity having at least 50 m 2 / g, and preferably at least 150m 2 / g surface area, a material with an apparent bulk density of 0.2g / ml to 1.0g / ml, and is selected from: gamma alumina, delta alumina, eta alumina, theta alumina, silica / alumina, zeolites, non-zeolitic molecular sieves (NZMS), titania, zirconia and mixtures thereof. It should be noted that silica / alumina is not a physical mixture of silica and alumina, but means an acidic and amorphous material that has been co-gelled or co-precipitated. The term is well known in the art, see, for example, U.S. Patents 3,909,450; 3,274,124; and 4,988,659, all of which are incorporated by reference. Examples of zeolites include, but are not limited to, zeolite Y, zeolite X, zeolite L, zeolite beta, ferrierite, MFI, mordenite and erionite. Non-zeolitic molecular sieves (NZMS) are those containing elements other than aluminum and silicon and include silicoaluminophosphates (SAPOs) described in US Pat. No. 4,440,871, ELAPOs described in US Pat. No. 4,793,984, MeAPOs described in US Pat. No. 4,567,029.

[0013] The layers are applied by forming a slurry of the outer refractory oxide and then coating the inner core with the slurry by means well known in the art. Slurries of inorganic oxides can be prepared by means well known in the art, which typically involve the use of a peptizing agent. For example, any of the transition aluminas can be mixed with water and an acid such as nitric acid, hydrochloric acid or sulfuric acid to obtain a slurry. Alternatively, an alumina sol can be prepared, for example, by dissolving aluminum metal in hydrochloric acid and then mixing the alumina sol with an alumina powder.

[0014] It is also necessary that the slurry contains an organic binder that helps the layer material adhere to the inner core. Examples of such organic binders include, but are not limited to, polyvinyl alcohol (PVA), hydroxypropyl cellulose, methyl cellulose, and carboxymethyl cellulose. The amount of organic binder added to the slurry will vary significantly from 0.1% to 3% by weight of the slurry. The strength of the bond between the outer layer and the inner core can be measured by the amount of layer material lost during the wear test, i.e., the wear loss. The loss of the second refractory oxide due to wear is measured by stirring the catalyst, collecting fine particles, and calculating the wear loss. It has been found that by using an organic binder as described above, the wear loss is less than 10% by weight of the outer layer. Finally, the thickness of the outer layer varies between 5 microns and 150 microns. One micron is equal to 10 -6 rice.

[0015] Depending on the particle size of the outer refractory inorganic oxide, it may be necessary to grind the slurry in order to reduce the particle size and simultaneously obtain a narrower particle size distribution. This can be accomplished by means known in the art (such as ball milling) and lasting 30 minutes to 5 hours, and preferably 1.5 hours to 3 hours. It has been found that the use of a slurry with a narrow particle size distribution improves the bonding of the outer layer to the core.

[0016] Without wishing to be bound by any particular theory, it appears that a binder such as PVA helps to form interlocking bonds between the outer layer material and the inner core. It is not clear whether this occurs by PVA reducing the surface tension of the core or by some other mechanism. Clearly, a significant reduction in outer layer loss due to wear is observed.

[0017] The slurry may also contain an inorganic binder selected from an alumina binder, a silica binder, or a mixture thereof. Examples of silica binders include silica sol and silica gel, while examples of alumina binders include alumina sol, boehmite, and aluminum nitrate. The inorganic binder is converted to alumina or silica in the finished composition. The amount of the inorganic binder varies between 2% and 15% by weight, measured as oxide and based on the weight of the slurry.

[0018] Coating the inner core with the slurry can be achieved by means such as roller coating, dipping, spraying, etc. A preferred technique involves using a fixed fluidized bed of inner core particles and spraying the slurry into the bed to uniformly coat the particles. The thickness of the layer can vary significantly, but is typically 40 microns to 150 microns. It should be noted that the optimal layer thickness depends on the choice of the outer refractory oxide. Once the inner core is coated with the outer refractory inorganic oxide layer, the resulting layered support is dried at a temperature of 100° C. to 320° C. for a time of 1 hour to 24 hours, and then calcined at a temperature of 400° C. to 1100° C. for a time of 0.5 hour to 10 hours to effectively bond the outer layer to the inner core and provide a layered catalyst support. Of course, the drying and calcining steps can be combined into one step.

[0019] When the inner core is composed of a refractory inorganic oxide (inner refractory oxide), the outer refractory inorganic oxide must be different from the inner refractory oxide. In addition, the inner refractory inorganic oxide is required to have a significantly lower adsorption capacity for catalytic metal precursors than the outer refractory inorganic oxide.

[0020] After obtaining the layered catalyst support, the catalytic metal can be dispersed on the layered support by means known in the art. Thus, the platinum group metal, the promoter metal and the modifier metal can be dispersed on the outer layer. The platinum group metal includes platinum, palladium, rhodium, iridium, ruthenium and osmium. The promoter metal is selected from the group consisting of tin, germanium, rhenium, gallium, bismuth, lead, indium, cerium, zinc and mixtures thereof, and the modifier metal is selected from the group consisting of alkali metals, alkaline earth metals and mixtures thereof.

[0021] These catalytic metal components can be deposited on the layered support in any suitable manner known in the art. One method involves impregnating the layered support with a solution (preferably aqueous) of a decomposable compound of one or more metals. By decomposable is meant that the metal compound is converted into a metal or metal oxide and releases byproducts when heated. Examples of decomposable compounds of the platinum group metals are chloroplatinic acid, ammonium chloroplatinate, bromoplatinic acid, dinitrodiaminoplatinum, sodium tetranitroplatinate, rhodium trichloride, hexaammonium rhodium chloride, carbonyl rhodium chloride, sodium hexanitrorhodiumate, chloropalladic acid, palladium chloride, palladium nitrate, diammine palladium hydroxide, tetraammine palladium chloride, hexachloroiridic acid (IV), hexachloroiridic acid (III), ammonium hexachloroiridate (III), hydrated ammonium hexachloroiridate (IV), ruthenium tetrachloride, hexachlororuthenate, hexaammine ruthenium chloride, osmium trichloride, and ammonium osmium chloride. Examples of decomposable promoter metal compounds are halide salts of promoter metals. The preferred promoter is tin, and the preferred decomposable compound is stannous chloride or stannic chloride.

[0022] Alkali metals and alkaline earth metals that can be used as modifier metals in the practice of the present invention include lithium, sodium, potassium, cesium, rubidium, beryllium, magnesium, calcium, strontium and barium. Preferred modifier metals are lithium, potassium, sodium and cesium, with lithium and sodium being particularly preferred. Examples of decomposable compounds of alkali metals and alkaline earth metals are halides, nitrates, carbonates or hydroxide compounds, such as potassium hydroxide, lithium nitrate.

[0023] All three types of metals may be impregnated using one common solution, or all three types of metals may be impregnated sequentially in any order, but not necessarily with the same results. A preferred impregnation procedure involves the use of a rotary dryer with a steam jacket. The support is immersed in an impregnation solution containing the desired metal compound contained in the dryer, and the support is tumbled therein by the rotary motion of the dryer. The evaporation of the solution in contact with the tumbling support is accelerated by applying steam to the dryer jacket. The resulting composite material is dried under ambient temperature conditions, or dried at a temperature of 80°C to 350°C, and then calcined at a temperature of 200°C to 700°C for a period of 1 hour to 4 hours to convert the metal compound to a metal or metal oxide. It should be noted that for platinum group metal compounds, calcination at a temperature of 400°C to 700°C is preferred.

[0024] In one method of preparation, the promoter metal is first deposited onto the layered support and calcined as described above, and then the modifier metal and platinum group metal are simultaneously dispersed onto the layered support by using an aqueous solution containing a compound of the modifier metal and a platinum group metal compound. The support is impregnated with the solution as described above and then calcined at a temperature of 400° C. to 700° C. for a period of 1 hour to 4 hours.

[0025] An alternative preparation method involves adding one or more metal components to an outer refractory oxide which is then applied as a layer to the inner core. For example, a decomposable salt of a promoter metal, such as tin (IV) chloride, may be added to a slurry consisting of gamma alumina and aluminum sol. In addition, a modifier metal or a platinum group metal, or both, may be added to the slurry. Thus, in one method, all three catalytic metals are deposited onto the outer refractory oxide prior to depositing the second refractory oxide onto the inner core in a layer. Likewise, the three types of catalytic metals may be deposited onto the outer refractory oxide powder in any order, but not necessarily with the same results.

[0026] Another preparation method involves first impregnating the promoter metal onto the outer refractory oxide and calcining as described above. Next, a slurry is prepared using the outer refractory oxide containing the promoter metal (as described above) and applied to the inner core in the manner described above. Finally, the modifier metal and platinum group metal are simultaneously impregnated onto the layered composition containing the promoter metal and calcined as described above to obtain the desired layered catalyst.

[0027] As the final step in preparing the layered catalyst composition, the catalyst composition is reduced under hydrogen or other reducing atmospheres to ensure that the platinum group metal component is in a metallic state (zero valence). The reduction is carried out in a reducing environment (preferably dry hydrogen) at a temperature of 100° C. to 650° C. for a time of 0.5 to 10 hours. The state of the promoter and modifier metals can be metal (zero valence), metal oxide or metal oxychloride.

[0028] The layered catalyst composition may also contain a halogen component, which may be fluorine, chlorine, bromine, iodine or a mixture thereof, wherein chlorine and bromine are preferred. Relative to the weight of the entire catalyst composition, the halogen component is present in an amount of 0.03 % by weight to 1.5 % by weight. The halogen component may be applied in a manner well known in the art, and may be carried out at any point during the preparation of the catalyst composition, but may not necessarily have the same result. Preferably, the halogen component is added before or after the hydrogen treatment after all catalytic components have been added.

[0029] Although in the preferred embodiment, all three metals are uniformly distributed throughout the outer layer of the outer refractory oxide and are substantially present only in the outer layer, it is also within the scope of the invention that the modifier metal may be present in both the outer layer and the inner core. This is due to the fact that when the core is not a metallic core, the modifier metal can migrate to the inner core.

[0030] Although the concentration of each metal component can vary significantly, it is desirable that the platinum group metal is present in a concentration of 0.01% to 5.0% by weight, preferably 0.05% to 2.0% by weight, based on the total weight of the catalyst. The promoter metal is present in an amount of 0.01% to 5.0% by weight of the entire catalyst, while the modifier metal is present in an amount of 0.01% to 5% by weight of the entire catalyst. Finally, the atomic ratio of the platinum group metal to the promoter metal varies between 0.05 and 5. Specifically, when the promoter metal is tin, the atomic ratio is 0.1:1 to 5:1, and preferably 0.5:1 to 3:1. When the promoter metal is germanium, the ratio is 0.25:1 to 5:1, and when the promoter metal is rhenium, the ratio is 0.05:1 to 2.75:1.

[0031] When the platinum group metal is platinum, the concentration is from 0.01 wt% to 5.0 wt% platinum on an elemental basis and based on the weight of the outer layer. For a given concentration of the platinum group metal in the outer layer, there is a preferred atomic ratio of the platinum group metal to the promoter metal. For example, when the platinum concentration is between 0.5 wt% and 3 wt% platinum on an elemental basis and based on the weight of the outer layer, the preferred atomic ratio of platinum to tin is between 0.5:1 and 1.3:1, which increases with increasing platinum concentration. When the platinum group metal is platinum, the loading is from 0.0010 grams to 0.0060 grams of platinum per cubic centimeter of catalyst on an elemental basis.

[0032] In addition, the layered catalyst used in the method of the present invention has a critical concentration of platinum group metals in the outer layer. This concentration is generally 0.00006 grams to 0.0005 grams of platinum group metals per square meter of the surface area of ​​the outer layer based on the element. A higher concentration of platinum group loading per unit surface area is preferred. The higher concentration can be formed by an alumina phase with a thinner outer layer thickness and / or a lower surface area. Typically, transition aluminas (i.e., δ and θ) have a lower surface area than γ alumina. Therefore, the platinum group concentration per square meter of the surface area of ​​the outer δ alumina and / or θ alumina layer is higher than the platinum group concentration on the γ alumina with the same outer layer thickness. The outer layer of the layered catalyst has a larger pore size with δ alumina and / or θ alumina, which leads to minimization of the yield of aromatic compounds.

[0033] The surface area of ​​the alumina support can be measured by nitrogen adsorption according to the BET surface area measurement method. A nitrogen adsorption BET measurement device ASAP 2010 from Micromeritics was used, and the multi-point BET measurement technique of DIN66131 was used. Sample amounts in the range of 0.1 g to 1.0 g can be used. For surface area measurements, 5 or more measurement points can be obtained in a relative pressure range (P / P0) of 0.05 to 0.25 from the adsorption isotherm. In one embodiment, the outer layer t of the alumina has a relative pressure of more than 70 m 2 / g or greater than 80m 2 / g or greater than 90m 2 In one exemplary embodiment, the outer layer of aluminum oxide has a surface area of ​​70 m 2 / g to 170m 2 / g of surface area.

[0034] The outer alumina layer may substantially comprise delta alumina and / or theta alumina. By "substantially delta alumina and / or theta alumina" is meant that the outer alumina layer comprises delta alumina and / or theta alumina in an amount greater than 99 wt%, or greater than 97 wt%, or greater than 95 wt%. The alumina crystallites of the outer alumina layer may comprise 100% delta alumina and / or theta alumina crystallites.

[0035] The delta alumina and / or theta alumina forms of crystalline alumina can be produced from an alumina precursor by strictly controlling the maximum calcination temperature experienced by the layered catalyst. Any suitable alumina precursor can be used to prepare the outer alumina layer of the present disclosure. In one embodiment, the alumina precursor can be boehmite. Instead of the typical gamma alumina conversion at a temperature of 500°C to 700°C, the applicant has found that to prepare the outer layer of delta alumina and / or theta alumina, the calcination temperature should be strictly controlled to 750°C to 1100°C or 800°C to 1050°C. Such calcination temperatures produce an outer layer of alumina comprising delta alumina and / or theta alumina crystallites. In addition, such calcination temperatures provide an outer layer of alumina having a particle size greater than 70 m 2 / g, or greater than 80m 2 / g or greater than 90m 2 / g of surface area of ​​delta alumina and / or theta alumina outer layer. In an exemplary embodiment, the alumina precursor can be calcined at a temperature of 750°C to 1100°C for a period of 10 minutes to 240 minutes to produce an alumina outer layer comprising delta alumina and / or theta alumina. It is known in the literature (Alumina properties. Technical Paper No. 10, revised 2nd by Newsome, JW; Heiser, HW; Russell, AS; Stumpf, HC) nd Revision by Newsome, JW; Heiser, HW; Russell, AS; Stumpf, HC)) When alumina is calcined at a higher temperature, the pore size of alumina is larger. Therefore, the pore size of the outer layer of delta alumina and / or theta alumina is generally larger than the pore size of gamma alumina.

[0036] The concentration of the platinum group metal in the outer layer can be readily determined in at least three ways. First, the concentration can be calculated based on the weight of the ingredients used to prepare the layered catalyst. Second, where the layered catalyst has been previously prepared and the inner refractory inorganic oxide is different from the outer refractory inorganic oxide, the inner layer refractory inorganic oxide can then be separated from the outer refractory inorganic oxide, and the platinum group metal can be recovered separately by known chemical and / or mechanical methods. The weight concentration of the platinum group metal can then be determined based on the weight of the recovered platinum group metal and the weight of the recovered inner refractory inorganic oxide. Finally, energy dispersive X-ray spectroscopy or wavelength dispersive spectroscopy (EPMA) using a scanning electron microscope can also be used on the layered catalyst sample.

[0037] After obtaining the layered catalyst, it can be used in the hydrocarbon dehydrogenation process. In the dehydrogenation zone maintained under dehydrogenation conditions, the dehydrogenatable hydrocarbon is contacted with the catalyst of the present invention. This contact can be achieved in a fixed catalyst bed system, a mobile catalyst bed system, a fluidized bed system, etc. or in an intermittent operation. A fixed bed system is preferred. In this fixed bed system, the hydrocarbon feed stream is preheated to the desired reaction temperature and then flows to the dehydrogenation zone containing the fixed catalyst bed. The dehydrogenation zone itself may include one or more separate reaction zones with a heating device between them to ensure that the desired reaction temperature can be maintained at the inlet of each reaction zone. The hydrocarbon can be contacted with the catalyst bed in an upward, downward or radial flow flow mode. It is preferred that the hydrocarbon flows radially through the catalyst bed. When the hydrocarbon contacts the catalyst, the hydrocarbon can be a liquid phase, a mixed gas-liquid phase or a gas phase. Preferably, it is in the form of a gas phase.

[0038] Dehydrogenatable hydrocarbons include hydrocarbons having 2 to 30 or more carbon atoms, including normal paraffins, isoparaffins, alkyl aromatics, cycloparaffins and olefins. A preferred group of hydrocarbons is the group of normal paraffins having 2 to 30 carbon atoms. Particularly preferred normal paraffins are normal paraffins having 9 to 16 carbon atoms. Other particularly preferred paraffins are monomethyl paraffins and dimethyl paraffins having 9 to 16 carbon atoms. Each of the aforementioned hydrocarbons may exist alone or in a mixture with one or more of any other aforementioned hydrocarbons.

[0039] The dehydrogenation conditions include a temperature of 400°C to 900°C, a pressure of 1 kPa to 1013 kPa, and a heating time of 0.1 hr. -1 Up to 100hr -1 The liquid hourly space velocity (LHSV) of the catalyst is 1.5 mol / L. As used herein, the abbreviation "LHSV" means liquid hourly space velocity, which is defined as the volumetric flow rate of liquid per hour divided by the volume of catalyst, wherein the liquid volume and the catalyst volume are in the same volume units. Generally, for paraffins, the lower the molecular weight, the higher the temperature required to achieve comparable conversion. The pressure in the dehydrogenation zone is maintained at as low a level as practicable, consistent with equipment limitations, to maximize chemical equilibrium advantage.

[0040] The effluent stream from the dehydrogenation zone will usually contain unconverted dehydrogenatable hydrocarbons, hydrogen and the product of the dehydrogenation reaction. These products include desired olefins and undesirable light ends, aromatic compounds, etc. This effluent stream is usually cooled and transferred to the hydrogen separation zone to separate the hydrogen-rich gas phase from the hydrocarbon-rich liquid phase. Usually, the hydrocarbon-rich liquid phase is further separated by suitable selective adsorbents, selective solvents, one or more selective reactions or by suitable fractionation schemes. Unconverted dehydrogenatable hydrocarbons are recovered and can be recycled to the dehydrogenation zone. The product of the dehydrogenation reaction is recovered as a final product or as an intermediate product for preparing other compounds. The aromatic compound formation (or yield) in the dehydrogenation zone must be minimized so that the aromatic compound concentration does not accumulate in the recycle stream and does not increase the size (and cost) of the selective adsorbent and solvent for removing it.

[0041] The novel layered catalyst of the present invention provides the formation of less aromatic compounds in the dehydrogenation zone. The combination of a platinum group concentration of 0.00006 to 0.0005 per square meter of outer layer surface area and a composition comprising delta alumina and / or theta alumina in the outer layer results in the formation of less aromatic compounds. Although the catalyst activity is still maintained by having a significant active metal platinum loading per cubic centimeter of catalyst or kilogram of outer layer as described in US6,756,515, the selectivity for the formation of aromatic compounds can be lowered by the delta alumina and / or theta alumina outer layer having an average pore size greater than the average pore size in the gamma alumina layer. Aromatic products are formed by the continuous dehydrogenation of desired olefins. The larger alumina pores in delta alumina and / or theta alumina allow olefins to diffuse faster and therefore do not undergo undesirable dehydrogenation to become aromatic compounds.

[0042] The dehydrogenatable hydrocarbon stream may be mixed with a diluent material before, simultaneously with, or after it is passed to the dehydrogenation zone. The diluent material may be hydrogen, steam, methane, ethane, carbon dioxide, nitrogen, argon, or the like, or a mixture thereof. Hydrogen is a preferred diluent. Typically, when hydrogen is utilized as a diluent, the amount used should be sufficient to ensure that the molar ratio of hydrogen to hydrocarbon is from 0.1:1 to 40:1, with best results being obtained when the molar ratio ranges from 1:1 to 10:1. The diluent hydrogen stream delivered to the dehydrogenation zone will typically be recycled hydrogen separated from the effluent from the dehydrogenation zone in the hydrogen separation zone.

[0043] For example, water or a material that decomposes to form water under the dehydrogenation conditions (such as an alcohol, aldehyde, ether or ketone) may be added continuously or intermittently to the dehydrogenation zone in an amount to provide less than 10,000 ppm by weight, preferably less than 5,000 ppm by weight, more preferably less than 3,000 ppm by weight, and possibly even less than 1,000 ppm by weight of the hydrocarbon feed stream calculated on an equivalent amount of water. The process of the present invention may be operated without water or a material that decomposes to form water being added to the dehydrogenation zone.

[0044] The following examples are provided by way of illustration of the invention and are not intended to unduly limit the generally broad scope of the invention as set forth in the appended claims.

[0045] Example 1

[0046] Alumina spheres are prepared by the well-known oil drop method, which is described in U.S. Pat. No. 2,620,314. The method involves forming an aluminum hydrosol by dissolving aluminum in hydrochloric acid. Hexamethylenetetramine is added to the sol to gel the sol into spheres when the droplets are dispersed into an oil bath maintained at 93°C. The droplets are retained in the oil bath until they solidify and form hydrogel spheres. After the spheres are removed from the hot oil, they are pressure aged at 135°C, and washed with a dilute ammonium hydroxide solution, dried at 110°C, and calcined at 650°C for 2 hours to obtain gamma alumina spheres. The calcined alumina is then crushed into a fine powder with a particle size of less than 200 microns.

[0047] Next, a slurry is prepared by mixing and stirring pseudoboehmite and deionized water to evenly distribute the tin component. To this mixture is added the above-prepared alumina powder and a 50% tin (IV) chloride aqueous solution, and the slurry is ball-milled for 240 minutes to reduce the maximum particle size to less than 50 microns. This slurry is sprayed onto a cordierite core having an average diameter of 1.6 mm using a granulation and coating apparatus to obtain an outer layer of 25 microns. At the end of the process, some slurry is left with the core uncoated. The layered spherical carrier is calcined at 900°C to convert the pseudoboehmite and gamma alumina in the outer layer into delta alumina, and to convert the tin chloride into tin oxide.

[0048] The calcined layered support was impregnated with lithium and platinum using a rotary impregnator by contacting the support with an aqueous solution containing lithium chloride and chloroplatinic acid (1:1 solution: support volume ratio) (based on the support weight). The impregnated composite material was heated using a rotary impregnator until no solution remained, dried at 315°C, calcined at 540°C, and reduced in hydrogen at 500°C. The resulting catalyst prepared in this example contained 0.1% to 0.2% by weight of platinum, 0.1% to 0.2% by weight of tin, and 0.1% to 0.2% by weight of lithium relative to the entire catalyst. These catalysts are identified as catalysts A, B, C, and D. The characteristics of catalysts A, B, C, and D are summarized in Table 1.

[0049] Table 1

[0050]

[0051] Example 2

[0052] The dehydrogenation activity of catalysts A, B, C and D from Example 1 was tested in a laboratory scale apparatus. In a 1.27 cm reactor, 5 cc of catalyst was placed and the reaction mixture was heated to 100 rpm at a pressure of 138 kPa (or 20 psig), a hydrocarbon molar ratio of 4:1, and 28 hr. -1 At a liquid hourly space velocity (LHSV), the concentration of nC 10 , 40.0 wt% to 41.8 wt% nC 11 、38.6wt%nC 12 , 8.6 wt% to 10.8 wt% nC 13 , 0.3 wt% to 0.8 wt% nC 14 A hydrocarbon feed consisting of 1 wt% to 1.4 wt% of non-normal isomers flows through the catalyst. The total normal olefin concentration (TNO%) in the product is maintained at 10 wt% by adjusting the reactor temperature.

[0053] The hydrogen and hydrocarbon feeds were combined upstream of the reactor to form a combined feed, and the combined feed was vaporized prior to entering the reactor. In this example, the catalysts were tested at a water concentration of 2000 wt-ppm based on the weight of hydrocarbons in the combined feed. Results for the product liquids collected at 48 hours for the four listed catalysts are presented in Table 2.

[0054] The feed and product streams were analyzed for aromatic content by utilizing backflushing on a high performance liquid chromatography (HPLC) system using n-hexane solvent as the mobile phase and a refractive index detector.

[0055] Normal paraffin conversion % = (normal paraffin in feed - normal paraffin in product) x 100% / normal paraffin in feed. Aromatic selectivity % = (aromatic compounds in product - aromatic compounds in feed) x 100% / normal paraffin conversion.

[0056] Even though Catalyst B shows lower aromatic selectivity than Catalyst A, its aromatic selectivity is still higher than those from Catalysts C and D. Therefore, one or more transition alumina phases (delta alumina and / or theta alumina) are present in the form of layers and high Pt density (grams of Pt in the alumina layer / layer surface area (g / m 2 )) combination achieves minimal aromatic compound formation.

[0057] Table 2

[0058] Sample ID Aromatic compound selectivity (%) Catalyst A 2.18 Catalyst B 1.80 Catalyst C 1.60 Catalyst D 1.62

[0059] Example 3

[0060] The structure of the alumina layer or the presence of delta alumina of the four catalysts A, B, C and D of the present disclosure was determined by X-ray analysis as shown in the figure. An attempt was made to remove the outer layer material by placing 1 cc of calcined alkali in a small grinding container without grinding media. The samples were ground for different amounts of time depending on the speed at which powder was generated from the outer layer. The powders from the four catalytic composites were labeled as samples A, B, C and D.

[0061] The X-ray patterns of samples A, B, C and D were obtained using standard X-ray powder diffraction techniques. The irradiation source was a high-intensity X-ray tube operating at 40 kV and 44 mA. The diffraction pattern from copper K-α irradiation was obtained by suitable computer-based techniques. The flat compressed powder sample was continuously scanned at 8 ° 2θ to 90 ° 2θ. The interplanar spacing (d) was obtained by the position of the diffraction peak expressed as 2θ, in angstroms, where 2θ is the Bragg angle as observed by the digitized data. As will be appreciated by those skilled in the art, the determination of the diffraction angle (2θ) is subject to both human and mechanical errors, and the combination of errors can give each reported 2θ value an uncertainty of ± 0.4 ° 2θ.

[0062] Specific implementation plan

[0063] While the following is described in conjunction with specific embodiments, it should be understood that this description is intended to illustrate and not to limit the scope of the foregoing description and the appended claims.

[0064] The present invention provides a catalyst composite material, which has a layered composition, the layered composition comprises an inner core, an outer layer combined with the inner core, the outer layer comprises one or more transition aluminas, the transition aluminas have at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak in the range is at 32.7±0.4°2θ, and the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a thickness of less than 100 microns and has at least one platinum group metal and at least one promoter metal uniformly dispersed thereon, and the concentration of the at least one platinum group metal is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of surface area of ​​the outer layer on an elemental basis, the layered composition also has at least one modifier metal dispersed thereon, and the inner core refractory inorganic oxide and the outer refractory inorganic oxide are different materials. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the X-ray diffraction pattern has at least 2 peaks and / or shoulders between 43±0.4°2θ and 49±0.4°2θ. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the outer layer has a thickness between 5 microns and 65 microns. The catalyst composite material according to claim 1, wherein the outer layer has a thickness between 5 microns and 39 microns. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the alumina in the outer layer has 70m 2 / g to 170m 2 The catalyst composite material according to claim 1, wherein the alumina in the outer layer has a surface area of ​​80 m 2 / g to 130m 2 / g surface area. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the aluminum oxide in the outer layer has a surface area of ​​90m 2 / g to 110m 2 / g of surface area. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the core is selected from: alpha alumina, metal, theta alumina, silicon carbide, cordierite, zirconium oxide, titanium dioxide and mixtures thereof. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the platinum group metal is selected from: platinum, palladium, rhodium, iridium, ruthenium, osmium and mixtures thereof. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the promoter metal is selected from: tin, germanium, rhenium, gallium, bismuth, lead, indium, cerium, zinc and mixtures thereof. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the promoter metal is selected from: alkali metals, alkaline earth metals and mixtures thereof. One embodiment of the present invention is one, any or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the platinum group metal is platinum. An embodiment of the present invention is one, any or all of the prior embodiments in this paragraph through the first embodiment in this paragraph, wherein the promoter metal is tin. An embodiment of the present invention is one, any or all of the prior embodiments in this paragraph through the first embodiment in this paragraph, further comprising 0.01 wt % to 1.0 wt % of a platinum group metal, 0.01 wt % to 1.0 wt % of a promoter metal, and 0.01 wt % to 1.0 wt % of a modifier metal.

[0065] In another embodiment of the present invention, a hydrocarbon dehydrogenation method is provided, which includes contacting a hydrocarbon stream with a layered composition under dehydrogenation conditions to obtain a dehydrogenated product, wherein the layered composition comprises an inner core, an outer layer bonded to the inner core, the outer layer comprises one or more transition aluminas, the transition aluminas having at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak within the range is at 32.7±0.4°2θ, the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a diffraction angle of less than 1. 00 microns in thickness and having a platinum catalyst and at least one promoter metal uniformly dispersed thereon, and the concentration of the platinum catalyst is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of surface area of ​​the outer layer on an elemental basis, the layered composition also has at least one modifier metal dispersed thereon, the inner core refractory inorganic oxide and the outer refractory inorganic oxide are different materials, and the layered composition also has a loading of at least one platinum group metal of 0.0010 grams to 0.0060 grams of platinum group metal per cubic centimeter of the layered composition on an elemental basis. One embodiment of the present invention is one, any one, or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the dehydrogenation conditions include a temperature of 400°C to 900°C and a pressure of 1 kPa to 1013 kPa. One embodiment of the present invention is one, any one, or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the hydrocarbon stream comprises at least one C2-C30 hydrocarbon selected from normal paraffins, isoparaffins, alkyl aromatic compounds, cycloalkanes, and olefins. One embodiment of the present invention is one, any one or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the hydrocarbon stream comprises monomethyl paraffins or dimethyl paraffins. One embodiment of the present invention is one, any one or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the hydrocarbon stream comprises normal paraffins having 2 to 16 carbon atoms. One embodiment of the present invention is one, any one or all of the previous embodiments in this paragraph to the first embodiment in this paragraph, wherein the hydrocarbon stream comprises C9-C16 hydrocarbons selected from normal paraffins, monomethyl paraffins and dimethyl paraffins.

[0066] Although there is no further detailed description, it is believed that those skilled in the art can utilize the present invention to the greatest extent by using the foregoing description and can easily determine the essential characteristics of the present invention without departing from the spirit and scope of the present invention to make various changes and modifications of the present invention and adapt it to various usages and conditions. Therefore, the aforementioned preferred specific embodiments should be understood as merely illustrative and not to limit the rest of the present disclosure in any way, and are intended to cover various modifications and equivalent arrangements included within the scope of the appended claims.

[0067] In the foregoing, all temperatures are set forth in degrees Celsius and all parts and percentages are by weight unless otherwise indicated.

Claims

1. A catalyst composite material having a layered composition, the layered composition comprising an inner core, an outer layer bonded to the inner core, the outer layer comprising one or more transition aluminas, the transition aluminas having at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak within the range is at 32.7±0.4°2θ and the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a thickness of less than 100 microns and has at least one platinum group metal and at least one promoter metal uniformly dispersed thereon, and the concentration of the at least one platinum group metal is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of surface area of ​​the outer layer on an elemental basis, the layered composition also having at least one modifier metal dispersed thereon, the inner core refractory inorganic oxide and the outer refractory inorganic oxide are different materials, wherein the outer layer comprises delta alumina and / or theta alumina in an amount greater than 95 wt.%, The aluminum oxide in the outer layer has a thickness of 70 m 2 / g to 170m 2 / g of surface area.

2. The catalyst composite material according to claim 1, wherein the X-ray diffraction pattern has at least 2 peaks and / or shoulders between 43±0.4°2θ and 49±0.4°2θ.

3. The catalyst composite material of claim 1, wherein the outer layer has a thickness between 5 microns and 65 microns.

4. The catalyst composite material according to claim 1, wherein the alumina in the outer layer has a thickness of 80 m 2 / g to 130m 2 / g of surface area.

5. The catalyst composite material according to claim 1, wherein the inner core is selected from the group consisting of alpha alumina, metal, theta alumina, silicon carbide, cordierite, zirconia, titania, and mixtures thereof.

6. The catalyst composite material according to claim 1, wherein the platinum group metal is selected from the group consisting of platinum, palladium, rhodium, iridium, ruthenium, osmium and mixtures thereof.

7. The catalyst composite material of claim 1, wherein the promoter metal is selected from the group consisting of tin, germanium, rhenium, gallium, bismuth, lead, indium, cerium, zinc, and mixtures thereof, and the modifier metal is selected from the group consisting of alkali metals, alkaline earth metals, and mixtures thereof.

8. The catalyst composite material of claim 1, further comprising 0.01 wt% to 1.0 wt% of the platinum group metal, 0.01 wt% to 1.0 wt% of the promoter metal, and 0.01 wt% to 1.0 wt% of the modifier metal.

9. A hydrocarbon dehydrogenation method, the hydrocarbon dehydrogenation method comprising contacting a hydrocarbon stream with a layered composition under dehydrogenation conditions to obtain a dehydrogenated product, the layered composition comprising an inner core, an outer layer bonded to the inner core, the outer layer comprising one or more transition aluminas, the transition aluminas having at least two diffraction angle peaks between 32.0°2θ and 70.0°2θ, wherein the first diffraction angle peak within the range is at 32.7±0.4°2θ, the second diffraction angle peak is at 50.8±0.4°2θ, and the outer layer has a thickness of less than 100 microns and has having the platinum catalyst and at least one promoter metal uniformly dispersed thereon, and the concentration of the platinum catalyst is 0.00006 grams to 0.0005 grams of platinum group metal per square meter of surface area of ​​the outer layer on an elemental basis, the layered composition further having at least one modifier metal dispersed thereon, the inner core refractory inorganic oxide and the outer refractory inorganic oxide are different materials, and the layered composition further has a loading of the at least one platinum group metal of 0.0010 grams to 0.0060 grams of platinum group metal per cubic centimeter of the layered composition on an elemental basis, wherein the outer layer comprises delta alumina and / or theta alumina in an amount greater than 95 wt.%, The aluminum oxide in the outer layer has a thickness of 70 m 2 / g to 170m 2 / g of surface area.

Citation Information

Patent Citations

  • Spheroidal alumina

    US2620314A

  • Process of preparing a silica-alumina supported group viii metal hydrocracking catalyst

    US3274124A

  • Catalytic composite of platinum tin and germanium with carrier material and reforming therewith

    US3632503A

  • Multicomponent dehydrogenation catalyst

    US3682838A

  • Dehydrogenation method and multicomponent catalytic composite for usetherein

    US3755481A